Studies on the Impact of Various Cultivation Practices on Phytochemical Parameters of Broccoli - Meena, Pooran Mal; Aggarwal, R. K.; Thakur, Abhimanyu (International Journal of Economic Plants, 2024)
The experiment on studies on the impact of various cultivation practices on phytochemical parameters of Broccoli (Brassica oleracea var. italica L.) was conducted during the rabi season of 2021–2022 with 3 transplanting dates (8th October, 28th October and 18th November 2021) followed by 3 subsequent harvesting dates (29th January, 8th March and 19th February, 2022) at the Research Farm, Department of Environmental Science, College of Forestry, Dr Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India. After harvesting the crop different phytochemical parameters were analysed for studying the effects of different treatments. The highest content of various phytochemical compounds like Total Soluble Solids (TSS), carotenoids, total phenols, glucosinolates, ascorbic acid, protein, total sugar, total chlorophyll, antioxidants, titratable acidity, anthocyanin, total lipids, etc. was reported in crop sown in the mid-season during the first week of October and followed by transplanting at the end of the same month. The mulching and irrigation practices also led to have increased concentration of these biochemical components in the Broccoli. In the case of mid-season transplanted, mulched and irrigated broccoli, the various biochemical compounds like carotenoids, total phenols, glucosinolates, ascorbic acid, protein, chlorophyll, anthocyanins and total antioxidants were reported 26.32, 20.13,10.27, 58.42, 16.56, 27.03, 28.70 and 16.76% respectively higher than the control samples and these cultivation practices were further recommended for the quality production of broccoli.